Elite Conflict of the Free Aceh Movement - Said Furqan (Institute of Computer Science (IOCS), 2020)
Aceh Party is a political party which is a local specialty party of former GAM’s combatant. After the determination the name of Dr. Zaini Abdullah and Muzakkir Manaf as Prospective Candidates for Governor and Vice Governor of Aceh’s Party in 2011, split within the Party of Aceh, immediately surfaced to the officials public of Aceh’s party, Kamaruddin and Sofyan Dawood in war opinion involved the mass opinion. the conflict between elite’s party occurs because the unilateral decision made in the Aceh’s Party leader Determination that both Dr. Zaini Abdullah and Muzakkir Manaf as Prospective Candidates for Governor and Vice Governor are not through the appropriate mechanisms of AD/ART (Charter/Bylaw). Therefore, the author is focused in the case of internal conflict in Aceh’s Party. This study aims to determine the cause of the conflict as well as describe and analyze the shape of the internal conflict in Aceh’s Party between senior and junior elite party. The results of this study indicate that the internal conflict in Aceh’s elite Party comes from differences nominations between senior and junior elite party to become candidates in Governor and Vice Governor of Aceh. The conflict in DPA’s (Central Area) level of Aceh’s Party creep up to the DPW’s (Board Area) perhaps creep up to the public level with a change of central area, some of board area’s Chairman and Aceh Party cadres are considered partial to junior’s elite. This conflict is also due to the divergence of interests between the elites residing in Aceh’ Party, as well as the internal factionalism bipolar stronghold of the senior and junior elite’s faction that formed because of differing views on the establishment of Candidates for Governor and Deputy Governor from the Aceh’s Party. This conflict including into realistic and latent conflict because the roots are shallow rooted and do not arise simply because of a misunderstanding about something that can be overcome by using communication.